Evaluation of Palm PCRTM G1-12 System: a portable battery-operated PCR thermal cycler - Ahmed, Siti Aminah; Hong, Leong Cheah; Ravichantar, Nithya; Gopinath, Subash C.B.; Thean, Hock Tang (Prince of Songkla University, 2016)
Polymerase chain reaction (PCR) is the basis of recombinant and other molecular biological techniques. Availability of cheap and robust PCR platforms enables the tests to be performed easily, even in resource constrained settings. Herein we compared the efficacy of a portable thermal cycler ( Palm PCRTM G1-12 System) for rapid DNA amplification against the standard Peltier-based thermal cycler using plasmid DNA and genomic DNA in single and multiplex PCR experiments. Our study revealed that the Palm PCRTM G1-12 System could be a portable DNA amplification system to conduct various molecular techniques, especially in places where resources are limited.